Kyrgyz Republic : Update on the Mining Sector - World Bank (Washington, DC, 2013)
The study, discussed at large with the Government of the Kyrgyz Republic, outlines several development objectives envisaged for the mining sector, namely, to maintain production, and social well-being at existing "kombinats"; to create competitive legal, and fiscal conditions, attractive to private sector investment; to increase the value added of the sector in terms of taxes, jobs, and induced spin-off industries; to sustain the sector's socioeconomic, and environmental performance; to provide acceptable conditions for closure of non-viable operations; and, to create a professional organization of public institutions. However, and despite government efforts to achieve the objectives, the study finds most of these are not being met. On reviewing the macroeconomic indicators for the country's mining sector, though some have increased since 1994, by and large are deceiving: employment in the sector has decreased, and, tax revenues are actually negative, implying a subsidy by the central treasury to the sector. Virtually all growth in the sector results from the Kumtor gold mine opened in 1997. Notwithstanding external factors outside government's control (price of gold) the study finds poor performance in the sector is due to deficiencies in the policy, legal and regulatory framework, and fiscal and institutional conditions pertaining to the industry. Findings point at the fundamental error by the Government, in taking direct equity participation in mining ventures, suggesting new tax policies to invert the excessively generous tax concessions, i.e., to apply a value added tax. Moreover, a revision to the Mining Law is essential, to provide easier access for exploration rights, and mining titles, including new legislative proposals, while strengthening institutions, professional competencies, environmental protection, and, adopting the United Nations Reserve Resources Classification system.